2004
DOI: 10.1139/z04-168
|View full text |Cite
|
Sign up to set email alerts
|

Movements and distribution of northern bottlenose whales,Hyperoodon ampullatus, on the Scotian Slope and in adjacent waters

Abstract: A small, apparently isolated, and endangered population of~130 northern bottlenose whales (Hyperoodon ampullatus Forster, 1770) is found on the Scotian Slope south of Nova Scotia, Canada. Virtually all previous information on these animals had come from the Gully, a large submarine canyon where the northern bottlenose whales can be reliably found. A ship survey along the 1000 m depth contour in 2001 showed northern bottlenose whales only in the Gully, Shortland canyon (50 km east of the Gully), and Haldimand c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 30 publications
2
67
0
1
Order By: Relevance
“…Analyses of dive behavior will be useful for examining foraging behavior within and outside of canyons. Shelf break canyons vary considerably in size, and previous studies have suggested that large canyons are likely to support larger numbers of cetaceans than smaller features (Wimmer & Whitehead 2004). The largest canyon within our study area is Hudson Canyon, which is also the northernmost canyon targeted by foraging pilot whales in our study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Analyses of dive behavior will be useful for examining foraging behavior within and outside of canyons. Shelf break canyons vary considerably in size, and previous studies have suggested that large canyons are likely to support larger numbers of cetaceans than smaller features (Wimmer & Whitehead 2004). The largest canyon within our study area is Hudson Canyon, which is also the northernmost canyon targeted by foraging pilot whales in our study.…”
Section: Discussionmentioning
confidence: 74%
“…The Gully, a large submarine canyon off eastern Canada, was designated as a Marine Protected Area in 2004, due in large part to a small population of northern bottlenose whales Hyperoodon ampullatus occurring in this region and increasing threats due to oil and gas exploration and development (Whitehead et al 1997, Gowans et al 2000, Wimmer & Whitehead 2004. Hudson Canyon was recently nominated as a national marine sanctuary due to its importance as habitat to a variety of marine organisms, and our results suggest that sanctuary designation in Hudson Canyon could protect important foraging habitat for short-finned pilot whales.…”
Section: Discussionmentioning
confidence: 99%
“…During the summer, blue whales are reported from several areas in eastern Canadian waters, including the St. Lawrence Estuary (SLE) and the Gulf of St. Lawrence (GSL) (Ramp & Sears 2013), off southern Newfoundland near the French islands of St. Pierre et Miquelon (Desbrosse & Etcheberry 1987), and near or in some canyons along the shelf edge off N ova Scotia (Wimmer & Whitehead 2004, Whitehead 2013. Passive acoustic monitoring systems deployed in US waters also indicated the presence of blue whales both near and off the shelf edge in southern N ewfoundland and the Grand Banks (Clark 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been assumed that their general biology is similar and most are thought to be deep-diving squid eaters that live in small groups along continental shelf edges. However, much of the information on the biology of these whales is derived from stranded animals combined with extrapolation from data collected on the few species that can be observed at sea (e.g., Wimmer and Whitehead, 2004;McSweeney et al, 2007). Long-term cetacean sighting surveys off the east coast of the United States suggest that beaked whales cluster into ecological niches that are different from all other odontocetes (Schick et al, 2011).…”
Section: Introductionmentioning
confidence: 99%